Preparation method of composite electrode, composite electrode, photoelectric device and preparation method of photoelectric device

By combining electroless plating and physical coating, composite electrodes were prepared, which solved the problems of low stability of existing electrode materials and slow deposition rate and uncontrollable thickness of the preparation method, and achieved high stability and controllability of the electrode layer.

CN119677386APending Publication Date: 2025-03-21GUANGDONG JUHUA RES INST OF ADVANCED DISPLAY +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311211398.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-19
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The existing electrode materials have low stability, and the preparation method has problems such as slow deposition rate and uncontrollable thickness.

Method used

The first electrode layer is prepared by electroless plating method, and after the concentrated acid surface roughening treatment is performed, the second electrode layer is prepared by physical coating method to form a composite electrode.

Benefits of technology

The stability and bonding force of the electrode are improved, and the rapid and effective preparation of the electrode layer is achieved, and the thickness is highly controllable.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119677386A_ABST
    Figure CN119677386A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a composite electrode, the composite electrode, a photoelectric device and a preparation method thereof, and the preparation method of the composite electrode comprises the steps: preparing a first electrode layer on a substrate through chemical plating, and the first electrode layer comprises a first surface; performing surface roughening treatment on the first surface of the first electrode layer to obtain the first surface after surface roughening treatment; and preparing a second electrode layer on the first surface subjected to acid treatment through a physical coating method to obtain the composite electrode. The preparation method can be used for rapidly and effectively preparing the composite electrode with excellent performance, proper thickness and relatively strong binding force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrode technology, and in particular to a method for preparing a composite electrode, a composite electrode, a photoelectric device and a method for preparing the same. Background Art

[0002] Electrodes are widely used in various electronic devices to input or output current so that the devices can work under the drive of electrical energy.

[0003] At present, commonly used electrode materials include transparent oxide electrodes, metal electrodes, composite electrodes of transparent oxides and metals, graphene electrodes, carbon nanotube electrodes and alloy electrodes, etc. These electrodes have good conductivity.

[0004] However, the stability of electrodes prepared by existing preparation methods is relatively low and needs to be further improved. Summary of the invention

[0005] In view of this, the present application provides a method for preparing a composite electrode.

[0006] The embodiment of the present application is implemented as follows: a method for preparing a composite electrode comprises the following steps:

[0007] Providing a substrate and a chemical plating solution, and placing the chemical plating solution on the substrate to obtain a first electrode layer, wherein the first electrode layer includes a first surface;

[0008] Performing a surface roughening treatment on the first surface of the first electrode layer to obtain a first surface after the surface roughening treatment;

[0009] The second electrode layer is prepared on the first surface after the surface roughening treatment by physical plating method to obtain a composite electrode.

[0010] Optionally, in some embodiments, the chemical plating solution includes one or more of a silver plating solution, a copper plating solution, a gold plating solution, an aluminum plating solution, and a magnesium plating solution.

[0011] Optionally, in some embodiments, the chemical plating solution includes a metal salt, an organic solvent and a reducing agent.

[0012] Optionally, in some embodiments, the metal salt includes one or more of a silver salt, a copper salt, a gold salt, an aluminum salt and a magnesium salt, wherein the silver salt includes one or more of silver nitrate, silver acetate and silver cyanide, the copper salt includes one or more of copper nitrate, copper acetate and copper cyanide, the gold salt includes one or more of gold nitrate, gold acetate and gold cyanide, the aluminum salt includes one or more of aluminum nitrate, aluminum acetate and aluminum cyanide, and the magnesium salt includes one or more of magnesium nitrate, magnesium acetate and magnesium cyanide; and / or

[0013] The organic solvent comprises one or more of acetone, methanol and isopropanol; and / or

[0014] The reducing agent includes one or more of acetaldehyde and hydrazine hydrate; and / or

[0015] In the chemical plating solution, the mass ratio of the metal salt, the organic solvent and the reducing agent is 1:(2-5):(1-3).

[0016] Optionally, in some embodiments, after placing the chemical plating solution on the substrate, the method further includes: heating the chemical plating solution on the substrate, wherein the heating temperature is 50 to 70° C., and / or the heating time is 1 to 3 hours.

[0017] Optionally, in some embodiments, performing a surface roughening treatment on the first surface of the first electrode layer includes: performing a surface roughening treatment on the first surface of the first electrode layer using a concentrated acid.

[0018] Optionally, in some embodiments, the concentrated acid includes one or more of concentrated sulfuric acid, concentrated nitric acid and concentrated hydrochloric acid; and / or

[0019] The concentration of the concentrated acid is 1.6 to 4 g / mL; and / or

[0020] The surface roughening treatment time is 20 to 40 minutes; and / or

[0021] The roughness of the first surface after the surface roughening treatment is 0.5-1 nm.

[0022] Optionally, in some embodiments, the physical coating method includes thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion coating method, physical vapor deposition method, atomic layer deposition method or pulsed laser deposition method.

[0023] Optionally, in some embodiments, the physical coating rate of the physical coating method is 0.1-0.3 nm / s; and / or

[0024] The physical plating time of the physical plating method is 200 to 300 seconds.

[0025] Optionally, in some embodiments, the physical coating material used in the physical coating method includes a second metal element, a second alloy or a doped metal oxide, wherein the second metal element includes one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba; the second alloy includes silver-copper alloy, silver-nickel alloy, aluminum-magnesium alloy, aluminum-magnesium-zinc-copper alloy, and gold-magnesium alloy; the doped metal oxide includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide, and cadmium-doped zinc oxide.

[0026] Optionally, in some embodiments, the chemical plating solution includes a silver plating solution, and the physical plating material used in the physical plating method includes Ag; or

[0027] The chemical plating solution includes a silver plating solution and a copper plating solution, and the physical plating material used in the physical plating method includes Ag; or

[0028] The chemical plating solution includes a silver plating solution, and the physical plating material used in the physical plating method includes Al; or

[0029] The chemical plating solution includes a silver plating solution, and the physical plating materials used in the physical plating method include Ag and Cu; or

[0030] The chemical plating solution includes a silver plating solution, and the physical plating material used in the physical plating method includes aluminum-doped magnesium oxide.

[0031] Correspondingly, an embodiment of the present application further provides a composite electrode, comprising a stacked first electrode layer and a second electrode layer, wherein the first electrode layer has a first surface, the second electrode layer is bonded to the first surface, and the roughness of the first surface is 0.5 to 1 nm.

[0032] Optionally, in some embodiments, the thickness of the first electrode layer is in the range of 10 to 30 nm; and / or

[0033] The thickness of the second electrode layer is in the range of 20 to 90 nm; and / or

[0034] The material of the first electrode layer includes a first metal element or a first alloy, wherein the first metal element includes one or more of silver, copper, gold, aluminum, and magnesium, and the first alloy includes a silver-copper alloy, a silver-nickel alloy, a silver-magnesium alloy, an aluminum-magnesium alloy, an aluminum-magnesium-zinc-copper alloy, or a gold-magnesium alloy; and / or

[0035] The material of the second electrode layer includes a second metal element, a second alloy or a doped metal oxide, wherein the second metal element includes one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba, the second alloy includes silver-copper alloy, silver-nickel alloy, aluminum-magnesium alloy, aluminum-magnesium-zinc-copper alloy, and gold-magnesium alloy, and the doped metal oxide includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide, and cadmium-doped zinc oxide.

[0036] Accordingly, the present invention also provides a method for preparing a photoelectric device, comprising the following steps:

[0037] providing a substrate, and preparing a first electrode on the substrate;

[0038] preparing a functional layer on the first electrode;

[0039] Prepare a second electrode on the surface of the functional layer away from the first electrode to obtain a photoelectric device;

[0040] Wherein, the first electrode and / or the second electrode are prepared by the above-mentioned preparation method of the composite electrode.

[0041] Optionally, in some embodiments, the functional layer includes one or more of a hole injection layer, a hole transport layer, a light emitting layer, and an electron transport layer.

[0042] Optionally, in some embodiments, the material of the hole injection layer includes one or more of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO3 derivatives, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide; and / or

[0043] The hole transport layer includes materials such as 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N '-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(N-vinylcarbazole) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4-4'-diamine, spiro NPB, poly(phenylene) 1,3-di(carbazol-9-yl)benzene, polyaniline, polypyrrole, poly(p-phenylene vinylene), aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(4-methoxyphenyl)amino)-1,4-phenylene vinylene, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], ... One or more of (p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; and / or

[0044] The material of the light-emitting layer includes one or more of an organic light-emitting material and a quantum dot light-emitting material, and the organic light-emitting material includes one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, thermally activated delayed materials, polymers containing covalent bonds of BN, hybrid localized charge transfer excited state materials, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;The quantum dot luminescent material includes one or more of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are independently selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, Zn STe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, One or more of PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound includes GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlN As, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor or an organic-inorganic hybrid perovskite semiconductor, and the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; and / or

[0045] The material of the electron transport layer includes one or more of an inorganic electron transport material and an organic electron transport material. The inorganic electron transport material includes one or more of a metal oxide, a doped metal oxide, a IIB-VIA semiconductor material, a IIIA-VA semiconductor material and an IB-IIIA-VIA semiconductor material. The metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO2 and Ta2O5. The metal oxide in the doped metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5 and Al2O3. The dopants in the oxide include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, and Sn; the IIB-VIA semiconductor materials include one or more of ZnS, ZnSe, and CdS; the IIIA-VA semiconductor materials include one or more of InP and GaP; the IB-IIIA-VIA semiconductor materials include one or more of CuInS and CuGaS; the organic electron transport material includes one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds.

[0046] Correspondingly, an embodiment of the present application also provides a photoelectric device, including a first electrode and a second electrode arranged opposite to each other, and a functional layer arranged between the first electrode and the second electrode, wherein the first electrode and / or the second electrode are prepared by the above-mentioned composite electrode preparation method.

[0047] Optionally, in some embodiments, the functional layer includes one or more of a hole injection layer, a hole transport layer, a light emitting layer, and an electron transport layer.

[0048] The preparation method of the composite electrode described in the present application first prepares a first electrode layer by chemical plating, then uses concentrated acid to perform surface treatment on the first electrode layer, and finally prepares a second electrode layer on the first electrode layer by physical plating. In this way, a composite electrode with excellent performance, appropriate thickness and strong bonding force can be prepared quickly and effectively. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.

[0050] Figure 1 This is a flow chart of a method for preparing a composite electrode provided in an embodiment of the present application;

[0051] Figure 2 is a schematic structural diagram of a composite electrode provided in an embodiment of the present application;

[0052] Figure 3 is a flow chart of a method for preparing a photoelectric device provided in an embodiment of the present application;

[0053] Figure 4 is a schematic structural diagram of an optoelectronic device provided in an embodiment of the present application;

[0054] Figure 5 It is a schematic diagram of the structure of another optoelectronic device provided in an embodiment of the present application.

[0055] Reference numerals:

[0056] Composite electrode 101; first electrode layer 11; first surface 111; second electrode layer 12; optoelectronic device 100; first electrode 10; functional layer 20; hole injection layer 21; hole transport layer 22; light emitting layer 23; electron transport layer 24; second electrode 30. DETAILED DESCRIPTION

[0057] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.

[0058] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.

[0059] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.

[0060] In the present application, "at least one" means one or more, and "plurality" means two or more. "At least one", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0061] In the present application, when a layer is formed "on" another layer, the so-called "on" is a broad concept, which may indicate that the formed another layer is adjacent to the certain layer, or may indicate that there are other spacing structural layers between the another layer and the certain layer. For example, when a second electrode is formed "on" the first carrier functional layer, the so-called "on" may indicate that the formed second electrode is adjacent to the first carrier functional layer, or may indicate that there are other spacing structural layers between the second electrode and the first carrier functional layer, such as a light-emitting layer.

[0062] Various embodiments of the present application may be presented in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity, and should not be understood as a rigid limitation on the scope of the present application; therefore, the range description should be considered to have specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, the range description from 1 to 6 should be considered to have specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the range, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated herein, it is meant to include any cited number (fractional or integer) within the indicated range.

[0063] Traditional methods for preparing metal electrodes are generally physical plating or chemical plating. Among them, the physical plating method has the problem of a fast deposition rate, which leads to inconsistent density of the deposited electrode layer, thus affecting the conductivity, stability, light reflectivity, etc. of the electrode; while the chemical plating method for preparing electrodes has a slow deposition rate and the thickness of the coating is uncontrollable.

[0064] The technical solution of this application is as follows:

[0065] First, see Figures 1-2 The present invention provides a method for preparing a composite electrode, comprising the following steps:

[0066] Step S11, providing a substrate and a chemical plating solution, placing the chemical plating solution on the substrate to obtain a first electrode layer 11, wherein the first electrode layer 11 includes a first surface 111;

[0067] Step S12, performing a surface roughening treatment on the first surface 111 of the first electrode layer 11 to obtain the first surface 111 after the surface roughening treatment;

[0068] Step S13, preparing the second electrode layer 12 on the first surface 111 after the surface roughening treatment by physical plating method to obtain the composite electrode 101.

[0069] The preparation method of the composite electrode described in the present application first prepares the first electrode layer 11 by chemical plating, then uses concentrated acid to perform surface treatment on the first electrode layer 11, and finally prepares the second electrode layer 12 on the first electrode layer 11 by physical plating. The first electrode layer 11 grown in situ by chemical plating has the advantages of smooth surface, high flatness, and density. The surface roughening treatment can increase the roughness of the first surface 111, thereby effectively improving the bonding force between the first electrode layer 11 and the second electrode layer 12. The physical plating method has the advantages of fast preparation speed and controllable thickness. In this way, a composite electrode 101 with excellent performance, suitable thickness and strong bonding force can be prepared quickly and effectively.

[0070] In the step S11:

[0071] The substrate may be a known substrate for preparing electrodes.

[0072] In some embodiments, the substrate is a rigid substrate or a flexible substrate, for example, including but not limited to one or more of glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide and polyether sulfone.

[0073] In other embodiments, the substrate may be a semi-device of an optoelectronic device with multiple composite electrodes to be prepared, such as a semi-device of an optoelectronic device including a stacked bottom electrode, a hole transport layer, a light-emitting layer and an electron transport layer.

[0074] The chemical plating solution is a known chemical plating solution used for preparing electrodes by chemical plating, such as one or more of a silver plating solution, a copper plating solution, a gold plating solution, an aluminum plating solution, and a magnesium plating solution.

[0075] In at least some embodiments, the chemical plating solution includes a metal salt, an organic solvent, and a reducing agent.

[0076] In some embodiments, in the chemical plating solution, the mass ratio of the metal salt, the organic solvent and the reducing agent is 1:(2-5):(1-3), for example, 1:2:1, 1:2.5:1, 1:3:1.5, 1:3.5:1.5, 1:4:2, 1:4.5:2, 1:5:2.5, etc.

[0077] The metal salt is a metal salt known to be used in chemical plating solutions, and may include, but is not limited to, one or more of silver salts, copper salts, gold salts, aluminum salts, and magnesium salts.

[0078] The silver salt includes, but is not limited to, one or more of silver nitrate, silver acetate, and silver cyanide.

[0079] The copper salt includes, but is not limited to, one or more of copper nitrate, copper acetate, and copper cyanide.

[0080] The gold salt includes, but is not limited to, one or more of gold nitrate, gold acetate, and gold cyanide.

[0081] The aluminum salt includes, but is not limited to, one or more of aluminum nitrate, aluminum acetate, and aluminum cyanide.

[0082] The magnesium salt includes, but is not limited to, one or more of magnesium nitrate, magnesium acetate, and magnesium cyanide.

[0083] The organic solvent may be a known organic solvent used in chemical plating solutions, for example, may include but is not limited to one or more of acetone, methanol, and isopropanol.

[0084] The reducing agent may be a known reducing agent used in chemical plating solutions, for example, may include but is not limited to one or more of acetaldehyde and hydrazine hydrate.

[0085] The material of the first electrode layer 11 includes but is not limited to a first metal element or a first alloy, the first metal element includes but is not limited to one or more of silver, copper, gold, aluminum, and magnesium, the first alloy includes but is not limited to silver-copper alloy, silver-nickel alloy, silver-magnesium alloy, aluminum-magnesium alloy, aluminum-magnesium-zinc-copper alloy or gold-magnesium alloy.

[0086] In some embodiments, after placing the chemical plating solution on the substrate, the process further includes: heating the chemical plating solution on the substrate. In this way, the speed and film-forming effect of chemical plating can be effectively improved, which is conducive to quickly and effectively preparing the first electrode layer 11 with good density and smooth surface.

[0087] The heating temperature is 50-70°C, for example, 50°C, 52°C, 54°C, 55°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C, 68°C, 70°C, etc., and the heating time is 1-3h, for example, 1h, 1.5h, 2h, 2.5h, 3h, etc. Within the temperature and time range, it is beneficial to quickly and effectively prepare the first electrode layer 11 with good density and smooth surface.

[0088] In some embodiments, the thickness of the first electrode layer 11 is in the range of 10 to 30 nm.

[0089] In step S12:

[0090] The roughening of the first surface 111 of the first electrode layer 11 includes: using concentrated acid to roughen the first surface 111 of the first electrode layer 11. The concentrated acid may include but is not limited to one or more of concentrated sulfuric acid, concentrated nitric acid and concentrated hydrochloric acid.

[0091] The concentration of the concentrated acid is 1.6-4 g / mL, for example, 1.6 g / mL, 1.8 g / mL, 2 g / mL, 2.2 g / mL, 2.5 g / mL, 2.6 g / mL, 2.8 g / mL, 3 g / mL, 3.2 g / mL, 3.5 g / mL, 3.6 g / mL, 3.8 g / mL, 4 g / mL, etc. Within the concentration range, the roughness of the first surface 111 of the first electrode layer 11 can be increased quickly and effectively.

[0092] The surface roughening treatment time is 20 to 40 minutes, for example, 20 minutes, 25 minutes, 30 minutes, 35 minutes, 40 minutes, etc. Within the time range, the roughness of the first surface 111 of the first electrode layer 11 can be increased quickly and effectively.

[0093] It can be understood that the method of using concentrated acid to perform surface treatment on the first surface 111 of the first electrode layer 11 can be to dispose the concentrated acid on the first surface 111 by a solution method.

[0094] It is understandable that when the substrate is a substrate that does not react with concentrated acid, such as glass, the method for surface treating the first surface 111 of the first electrode layer 11 with concentrated acid may be to immerse the first electrode layer 11 in concentrated acid.

[0095] In some embodiments, the roughness of the first surface 111 after the surface roughening treatment is 0.5-1 nm, for example, 0.5 nm, 0.6 nm, 0.8 nm, 0.9 nm, 1 nm, etc. Within the roughness range, the bonding force between the first electrode layer 11 and the second electrode layer 12 can be effectively improved.

[0096] In step S13:

[0097] The physical coating method includes but is not limited to any one of thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion coating method, physical vapor deposition method, atomic layer deposition method, and pulsed laser deposition method.

[0098] In some embodiments, preparing the second electrode layer 12 on the acid-treated first surface 111 by physical plating includes: providing a physical plating material, and depositing the physical plating material on the acid-treated first surface 111 by physical plating to obtain the second electrode layer 12.

[0099] The physical plating material includes but is not limited to a second metal element, a second alloy or a doped metal oxide. The second metal element includes but is not limited to one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba. The second alloy includes but is not limited to silver-copper alloy, silver-nickel alloy, aluminum-magnesium alloy, aluminum-magnesium-zinc-copper alloy, and gold-magnesium alloy. The doped metal oxide includes but is not limited to one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide, and cadmium-doped zinc oxide.

[0100] In some embodiments, the chemical plating solution includes a silver plating solution, and the physical plating material used in the physical plating method includes Ag. In this case, the first electrode layer 11 of the prepared composite electrode 101 includes Ag, and the second electrode layer 12 includes Ag, that is, the composite electrode 101 is Ag / Ag, which has good conductivity.

[0101] In some embodiments, the chemical plating solution includes a silver plating solution and a copper plating solution, and the physical plating material used in the physical plating method includes Ag. In this case, the first electrode layer 11 of the prepared composite electrode 101 includes Ag and Cu, and the second electrode layer 12 includes Ag, that is, the composite electrode 101 is Ag@Cu / Ag, which has good corrosion resistance.

[0102] In some embodiments, the chemical plating solution includes a silver plating solution, and the physical plating material used in the physical plating method includes Al. In this case, the first electrode layer 11 of the prepared composite electrode 101 includes Ag, and the second electrode layer 12 includes Al, that is, the composite electrode 101 is Ag / Al, which has good oxidation resistance and thermal conductivity.

[0103] In some embodiments, the chemical plating solution includes a silver plating solution, and the physical plating material used in the physical plating method includes Ag and Cu. In this case, the first electrode layer 11 of the prepared composite electrode 101 includes Ag, and the second electrode layer 12 includes Ag and Cu, that is, the composite electrode 101 is Ag / Ag@Cu, which has good oxidation resistance and high temperature resistance.

[0104] In some embodiments, the chemical plating solution includes a silver plating solution, and the physical plating material used in the physical plating method includes aluminum-doped magnesium oxide. In this case, the first electrode layer 11 of the prepared composite electrode 101 includes Ag, and the second electrode layer 12 includes Al-doped MgO, that is, the composite electrode 101 is Ag / Al-doped MgO, which has good corrosion resistance and toughness.

[0105] In some embodiments, the physical coating rate of the physical coating method is 0.1-0.3 nm / s, for example, 0.1 nm / s, 0.2 nm / s, 0.3 nm / s, etc., and the physical coating time of the physical coating method is 200-300 s, for example, 200 s, 220 s, 250 s, 260 s, 280 s, 300 s, etc. Within the rate and time range, it is beneficial to quickly and effectively prepare the second electrode layer 12 with a suitable thickness and good film-forming effect.

[0106] The material of the second electrode layer 12 includes the second metal element, the second alloy or the doped metal oxide.

[0107] It can be understood that the material of the first electrode layer 11 and the material of the second electrode layer 12 can be the same or different.

[0108] The thickness of the second electrode layer 12 is in the range of 20 to 90 nm.

[0109] Second, see Figure 2 The embodiment of the present application further provides a composite electrode 101 prepared by the above preparation method, comprising a stacked first electrode layer 11 and a second electrode layer 12 .

[0110] The first electrode layer 11 has a first surface 111 , and the second electrode layer 12 is combined on the first surface 111 . The roughness of the first surface 111 is 0.5-1 nm.

[0111] The thickness of the first electrode layer 11 is 10-30 nm. Within the thickness range, the first electrode layer 11 can be quickly and effectively prepared by chemical plating, and the surface flatness of the first electrode layer 11 is relatively high.

[0112] The thickness of the second electrode layer 12 is 20-90 nm. Within the thickness range, the second electrode layer 12 has good conductivity and high flatness, and can be matched with the thickness of the first electrode layer 11 to obtain a composite electrode 101 with a suitable thickness.

[0113] The material of the first electrode layer 11 includes but is not limited to a first metal element or a first alloy. The first metal element includes but is not limited to one or more of silver, copper, gold, aluminum, and magnesium, and the first alloy includes but is not limited to a silver-copper alloy, a silver-nickel alloy, a silver-magnesium alloy, an aluminum-magnesium alloy, an aluminum-magnesium-zinc-copper alloy, or a gold-magnesium alloy.

[0114] The material of the second electrode layer 12 includes a second metal element, a second alloy or a doped metal oxide. The second metal element includes, but is not limited to, one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba. The second alloy includes a silver-copper alloy, a silver-nickel alloy, an aluminum-magnesium alloy, an aluminum-magnesium-zinc-copper alloy, and a gold-magnesium alloy. The doped metal oxide includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide, and cadmium-doped zinc oxide.

[0115] Third, see Figures 3 to 5 The present application also provides a method for preparing a photoelectric device, comprising the following steps:

[0116] Step S21, providing a substrate and preparing a first electrode 10 on the substrate;

[0117] Step S22, preparing a functional layer 20 on the first electrode 10;

[0118] Step S23 , preparing a second electrode 30 on a surface of the functional layer 20 away from the first electrode 10 , to obtain a photoelectric device 100 .

[0119] The first electrode 10 is the composite electrode 101, and / or the second electrode 30 is the composite electrode 101. In other words, the first electrode 10 and / or the second electrode 30 are prepared by the composite electrode preparation method described above.

[0120] It can be understood that when the first electrode 10 or the second electrode 30 is the composite electrode described in the present application, the materials of the first electrode 10 and the second electrode 30 can be the same or different. In other words, when the first electrode 10 and the second electrode 30 are both composite electrodes 101, the materials and conditions for preparing the first electrode layer 11 and the second electrode layer 12 of the first electrode 10, the conditions for acid treatment and heating of the first electrode 10, and the materials and conditions for preparing the first electrode layer 11 and the second electrode layer 12 of the second electrode 30 can all be the same or different.

[0121] When one of the first electrode 10 and the second electrode 30 is not the composite electrode 101 described in the present application, the electrode that is not the composite electrode 101 described in the present application may include a doped metal oxide electrode, a composite electrode, a graphene electrode, a carbon nanotube electrode, a metal element electrode or an alloy electrode, and the material of the doped metal oxide electrode includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide, and cadmium-doped zinc oxide, and the composite electrode includes AZO / Ag / AZO, AZO / Al / AZO, ITO / A g / ITO, ITO / Al / ITO, ZnO / Ag / ZnO, ZnO / Al / ZnO, TiO2 / Ag / TiO2, TiO2 / Al / TiO2, ZnS / Ag / ZnS, ZnS / Al / ZnS, Ca / Al, LiF / Ca, LiF / Al, BaF2 / Al, CsF / Al, CaCO3 / Al or BaF2 / Ca / Al, the material of the metal single substance electrode includes one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba, and the alloy electrode includes Au:Mg alloy electrode or Ag:Mg alloy electrode.

[0122] The functional layer 20 includes one or more of a hole injection layer 21 , a hole transport layer 22 , a light emitting layer 23 , and an electron transport layer 24 .

[0123] The material of the hole injection layer 21 can also be a material known in the art for a hole injection layer, for example, it can be selected from but not limited to one or more of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene (HAT-CN), PEDOT, PEDOT:PSS, a derivative of PEDOT:PSS doped with s-MoO3 (PEDOT:PSS:s-MoO3), 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), tetracyanoquinodimethane (F4-TCQN), copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide.

[0124] The material of the hole transport layer 22 can be a material known in the art for a hole transport layer, for example, can be selected from but not limited to 4,4'-N,N'-dicarbazolyl-biphenyl (CBP), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA), N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine (TPD), poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine) (Poly-TPD), N ...1-naphthyl)-1,1'-biphenyl-4,4"-diamine (α-NPD), N (3-methylphenyl)-N,N'-bis(phenyl)-spiro(spiro-TPD), N,N'-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine (DNTPD), 4,4',4'-tri(N-carbazolyl)-triphenylamine (TCTA), 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine (m-MTDATA), poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))] (TFB), poly(N-vinylcarbazole) (PVK) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl -1,1'-biphenyl-4-4'-diamine (NPB), spiro NPB, poly(phenylene vinylene) (PPV), poly[2-methoxy-5-(2-ethylhexyloxy)-1,4-phenylene vinylene] (MEH-PPV), poly[2-methoxy-5-(3',7'-dimethyloctyloxy)-1,4-phenylene vinylene] (MOMO-PPV), 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene (spiro-omeTAD), 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline] (TAPC), 1,3-bis(carbazol-9-yl)benzene (MCP ), polyaniline, polypyrrole, poly(p-)phenylene vinylene, aromatic tertiary amine, polynuclear aromatic tertiary amine, 4,4'-bis(p-carbazolyl)-1,1'-biphenyl compound, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO. One or more.

[0125] In some embodiments, in the doped metal oxide particles, the mass fraction of the doping element in the doped metal oxide particles is 1-20%, for example, 1-10%, 5-15%, 8-18%, 10-20%, etc. Within the doping amount range, the stability and electron transport performance of the electron transport layer 24 can be effectively improved.

[0126] The material of the light-emitting layer 23 may include, but is not limited to, one or more of an organic light-emitting material and a quantum dot light-emitting material.

[0127] The organic light-emitting material may include, but is not limited to, one or more of CBP:Ir(mppy)3(4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III)), TCTX:Ir(mmpy)(4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium), diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, TADF (thermally activated delay) materials, polymers containing covalent bonds of BN, HLCT (hybridized localized charge transfer excited state) materials, Exciplex (exciplex) light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives.

[0128] The quantum dot light-emitting material may include, but is not limited to, one or more of single structure quantum dots, core-shell structure quantum dots and perovskite semiconductor materials.

[0129] The material of the single structure quantum dots, the core material of the core-shell structure quantum dots and the shell material of the core-shell structure quantum dots may respectively include but are not limited to one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds may include, but are not limited to, one or more of CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, ZnSTe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe. The IV-VI group compounds may include, but are not limited to, one or more of SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, and SnPbSTe. The III-V group compound may include, but is not limited to, one or more of GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlNAs, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs, and InAlPSb. The I-III-VI group compound may include, but is not limited to, one or more of CuInS2, CuInSe2, and AgInS2.

[0130] As an example, the core-shell structured quantum dots may include, but are not limited to, one or more of CdSe / CdSeS / CdS, InP / ZnSeS / ZnS, CdZnSe / ZnSe / ZnS, CdSeS / ZnSeS / ZnS, CdSe / ZnS, CdSe / ZnSe / ZnS, ZnSe / ZnS, ZnSeTe / ZnS, CdSe / CdZnSeS / ZnS and InP / ZnSe / ZnS.

[0131] The perovskite semiconductor material may include but is not limited to doped or undoped inorganic perovskite semiconductors, or organic-inorganic hybrid perovskite semiconductors. The inorganic perovskite semiconductor has a general structural formula of AMX3, wherein A is Cs + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - The general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of .

[0132] The material of the electron transport layer 24 is a material known in the art for electron transport layers, for example, it can be selected from but not limited to one or more of inorganic electron transport materials and organic electron transport materials. The inorganic electron transport material includes but is not limited to one or more of metal oxides, doped metal oxides, IIB-VIA semiconductor materials, IIIA-VA semiconductor materials and IB-IIIA-VIA semiconductor materials. Specifically, the metal oxide is selected from but not limited to one or more of ZnO, TiO2, SnO2, ZrO2, and Ta2O5; the metal oxide in the doped metal oxide is selected from but not limited to one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5, and Al2O3; the dopant in the doped metal oxide is selected from but not limited to one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, and Sn. For example, the doped metal oxide may be aluminum zinc oxide (AZO), lithium-doped zinc oxide (LZO), magnesium-doped zinc oxide (MZO), and tin-doped zinc oxide, etc.; the IIB-VIA semiconductor material is selected from but not limited to one or more of ZnS, ZnSe, and CdS; the IIIA-VA semiconductor material is selected from but not limited to one or more of InP and GaP; the IB-IIIA-VIA semiconductor material is selected from but not limited to one or more of CuInS and CuGaS. The organic electron transport material includes, but is not limited to, one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds.

[0133] It is understood that in some embodiments, the optoelectronic device 100 may also include functional layers conventionally used in optoelectronic devices to help improve the performance of optoelectronic devices, such as an electron blocking layer, a hole blocking layer, an electron injection layer, an interface modification layer, etc.

[0134] It can be understood that the materials of each layer of the optoelectronic device 100 can be adjusted according to the light emitting requirements of the optoelectronic device 100 .

[0135] In some embodiments, the optoelectronic device further includes a substrate, and the substrate is disposed on a surface of the first electrode 10 facing away from the light-emitting layer 23 , or the substrate is disposed on a surface of the second electrode 30 facing away from the light-emitting layer 23 .

[0136] The substrate may be a rigid substrate or a flexible substrate. In some embodiments, the material of the substrate may include but is not limited to one or more of glass, silicon wafer, polycarbonate, polymethyl methacrylate, polyethylene terephthalate, polyethylene naphthalate, polyamide and polyether sulfone.

[0137] It is understood that the optoelectronic device 100 may be an upright optoelectronic device or an inverted optoelectronic device. The optoelectronic device 100 may be a quantum dot optoelectronic device or an organic optoelectronic device.

[0138] The method for forming the hole injection layer 21, the hole transport layer 22, the light-emitting layer 23, and the electron transport layer 24 can be implemented by conventional techniques in the art, such as chemical methods or physical methods. Among them, the chemical method includes chemical vapor deposition, continuous ion layer adsorption and reaction, anodization, electrolytic deposition, and coprecipitation. The physical method includes the physical plating method and solution method described above, wherein the solution method can be spin coating, printing, inkjet printing, blade coating, printing, dip-pull method, immersion method, spray coating, roll coating, casting, slit coating, and strip coating, etc.

[0139] It can be understood that when the optoelectronic device 100 also includes functional layers conventionally used in optoelectronic devices that help improve the performance of the optoelectronic device, such as an electron blocking layer, a hole blocking layer, an electron injection layer, an interface modification layer, etc., the preparation method of the optoelectronic device 100 may also include the step of preparing the above-mentioned functional layers using conventional techniques in the field.

[0140] In a fourth aspect, an embodiment of the present application further provides an optoelectronic device 100 prepared by the preparation method described above.

[0141] In a fifth aspect, the present application also relates to a display device, which includes the optoelectronic device 100 .

[0142] The display device can be any electronic product with a display function, including but not limited to smart phones, tablet computers, laptops, digital cameras, digital video cameras, smart wearable devices, smart weighing electronic scales, car displays, televisions or e-book readers, among which smart wearable devices can be, for example, smart bracelets, smart watches, virtual reality (VR) helmets, etc.

[0143] The present application is described in detail below through specific embodiments. The following embodiments are only partial embodiments of the present application and are not limitations of the present application.

[0144] Example 1

[0145] Providing a conductive glass substrate having an ITO first electrode 10 (anode) with a thickness of 80 nm, cleaning the ITO conductive glass with a detergent to preliminarily remove stains on the surface, then ultrasonically cleaning in deionized water, acetone, anhydrous ethanol, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally drying with high-purity nitrogen;

[0146] In a glove box, spin-coat a PEDOT:PSS material on the first electrode 10 at a spin-coating speed of 5000 rpm for 30 seconds and anneal at 150° C. for 30 minutes to obtain a hole injection layer 21 with a thickness of 30 nm;

[0147] Spin coating TFB material on the hole injection layer 21, wherein the spin coating speed is 3000 rpm, the time is 30 s, and annealing is performed at 200° C. for 30 min to obtain a hole transport layer 22 with a thickness of 25 nm;

[0148] Spin coating CdZnSe quantum dots on the hole transport layer 22, wherein the spin coating speed is 2000 rpm, the time is 30 s, and annealing is performed at 80° C. for 5 min to obtain a light emitting layer 23 with a thickness of 30 nm;

[0149] Spin-coat the luminescent layer 23 with an ethanol solution of ZnO at a speed of 4000 rpm for 30 seconds and anneal at 80° C. for 30 minutes to obtain an electron transport layer 24 with a thickness of 35 nm;

[0150] A silver plating solution is provided, wherein the silver plating solution includes silver nitrate, oxalyl dihydrazide (hydrazine hydrate), acetone, and isopropanol, wherein the concentration of silver salt is 10wt%, the concentration of oxalyl dihydrazide is 10wt%, the mass concentration of acetone is 10wt%, and the mass concentration of isopropanol is 70wt%, and the silver plating solution is applied on the surface of the electron transport layer 24 by spray coating, and heated at 60° C. for 2h to obtain a first electrode layer 11 with a thickness of 20nm;

[0151] Coating concentrated sulfuric acid with a concentration of 2 g / ml on the first surface 111 of the first electrode layer 11 away from the electron transport layer 24, and after 30 minutes, cleaning the surface of the first electrode layer 11 to obtain the first surface 111 after acid treatment;

[0152] Ag is evaporated on the first surface at a rate of 0.2 nm / s for 250 s, and a second electrode layer 12 with a thickness of 80 nm is prepared on the first electrode layer 11 to obtain a composite electrode 101, i.e., a second electrode 30 (cathode);

[0153] The optoelectronic device 100 is obtained by packaging in an environment where both the oxygen content and the water content are lower than 0.1 ppm.

[0154] Example 2

[0155] This embodiment is basically the same as the embodiment 1, except that, in this embodiment, the heating temperature during the preparation of the first electrode layer 11 is 50° C.

[0156] Example 3

[0157] This embodiment is basically the same as the embodiment 1, except that, in this embodiment, the heating temperature during the preparation of the first electrode layer 11 is 70° C.

[0158] Example 4

[0159] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the heating time during the preparation of the first electrode layer 11 is 1 hour.

[0160] Example 5

[0161] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the heating time during the preparation of the first electrode layer 11 is 3 hours.

[0162] Example 6

[0163] This embodiment is substantially the same as embodiment 1 except that, in this embodiment, the concentration of concentrated sulfuric acid is 1.6 g / ml.

[0164] Example 7

[0165] This embodiment is substantially the same as Embodiment 1 except that, in this embodiment, the concentration of concentrated sulfuric acid is 4 g / ml.

[0166] Example 8

[0167] This embodiment is substantially the same as Embodiment 1 except that, in this embodiment, concentrated nitric acid with a concentration of 2 g / ml is used to replace concentrated sulfuric acid with a concentration of 2 g / ml in Embodiment 1.

[0168] Example 9

[0169] This embodiment is basically the same as Embodiment 1 except that, in this embodiment, silver cyanide is used to replace the silver nitrate in Embodiment 1.

[0170] Example 10

[0171] This embodiment is basically the same as Embodiment 1 except that, in this embodiment, silver nitrate and copper nitrate are used to replace the silver nitrate in Embodiment 1, and the mass concentration ratio of silver nitrate to copper nitrate is 1:1.

[0172] Embodiment 11

[0173] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the evaporation rate during the preparation of the second electrode layer 12 is 0.1 nm / s.

[0174] Example 12

[0175] This embodiment is basically the same as Embodiment 1, except that, in this embodiment, the evaporation rate during the preparation of the second electrode layer 12 is 0.3 nm / s.

[0176] Embodiment 13

[0177] This embodiment is basically the same as the embodiment 1, except that in this embodiment, when preparing the second electrode layer 12, Al is used to replace the Ag in the embodiment 1.

[0178] Embodiment 14

[0179] This embodiment is basically the same as the embodiment 1, except that, in this embodiment, when preparing the second electrode layer 12, Ag and Cu are used to replace the Ag in the embodiment 1.

[0180] Embodiment 15

[0181] This embodiment is basically the same as the embodiment 1, except that, in this embodiment, when preparing the second electrode layer 12, aluminum-doped magnesium oxide is used to replace Ag in the embodiment 1.

[0182] Example 16

[0183] Providing a glass substrate, cleaning the glass substrate with a detergent to preliminarily remove stains on the surface, then ultrasonically cleaning the glass substrate in deionized water, acetone, anhydrous ethanol, and deionized water for 20 minutes respectively to remove impurities on the surface, and finally drying the glass substrate with high-purity nitrogen;

[0184] A silver plating solution is provided, wherein the silver plating solution comprises silver salt silver nitrate, oxalyl dihydrazide (hydrazine hydrate), acetone, and isopropanol, wherein the concentration of the silver salt is 10wt%, the concentration of the oxalyl dihydrazide is 10wt%, the mass concentration of the acetone is 10wt%, and the mass concentration of the isopropanol is 70wt%, and the silver plating solution is applied on a surface of a glass substrate by spray coating, and heated at 60° C. for 2h to obtain a first electrode layer 11 with a thickness of 20nm;

[0185] Concentrated sulfuric acid with a concentration of 2 g / ml is coated on the first surface 111 of the electron transport layer 24 described in the principle of the first electrode layer 11. After 2 hours, the surface of the first electrode layer 11 is cleaned to obtain the first surface 111 after acid treatment;

[0186] Ag is evaporated on the first surface at a rate of 0.2 nm / s for 250 s, and a second electrode layer 12 with a thickness of 80 nm is prepared on the first electrode layer 11 to obtain a composite electrode 101, i.e., the first electrode 10 (cathode);

[0187] Spin coating the second electrode layer 12 with an ethanol solution of ZnO at a speed of 4000 rpm for 30 seconds and annealing at 80° C. for 30 minutes to obtain an electron transport layer 24 with a thickness of 35 nm;

[0188] Spin coating CdZnSe quantum dots on the electron transport layer 24, wherein the spin coating speed is 2000 rpm, the time is 30 s, and annealing is performed at 80° C. for 5 min to obtain a light emitting layer 23 with a thickness of 30 nm;

[0189] Spin coating TFB material on the light emitting layer 23, wherein the spin coating speed is 3000 rpm, the time is 30 s, and annealing is performed at 200° C. for 30 min to obtain a hole transport layer 22 with a thickness of 25 nm;

[0190] Spin coating PEDOT:PSS material on the hole transport layer 22, wherein the spin coating speed is 5000 rpm, the time is 30 s, and annealing is performed at 150° C. for 30 min to obtain a hole injection layer 21 with a thickness of 30 nm;

[0191] ITO is evaporated on the hole injection layer 21 to obtain a second electrode 30 (anode) with a thickness of 80 nm;

[0192] The optoelectronic device 100 is obtained by packaging in an environment where both the oxygen content and the water content are lower than 0.1 ppm.

[0193] Comparative Example 1

[0194] This comparative example is basically the same as Example 1, except that the preparation method of the second electrode in this comparative example is:

[0195] A silver plating solution is provided, wherein the silver plating solution includes silver nitrate, oxalic acid hydrazide (hydrazine hydrate), acetone, and isopropanol, wherein the concentration of the silver salt is 10wt%, the concentration of the oxalic acid hydrazide is 10wt%, the mass concentration of the acetone is 10wt%, and the mass concentration of the isopropanol is 70wt%. The silver plating solution is spray-coated on the surface of the electron transport layer, and heated at 60°C for 4h to obtain a second electrode with a thickness of 96nm.

[0196] Comparative Example 2

[0197] This comparative example is basically the same as Example 1, except that the preparation method of the second electrode in this comparative example is:

[0198] Ag was evaporated on the electron transport layer, wherein the evaporation rate was 0.2 nm / s for 500 s, and a second electrode with a thickness of 100 nm was prepared on the electron transport layer.

[0199] Comparative Example 3

[0200] This comparative example is substantially the same as Example 1, except that the first surface 111 of the first electrode layer 11 of this comparative example is not treated with concentrated sulfuric acid.

[0201] The binding force between the first electrode layer and the second electrode layer of the composite electrode of Examples 1 to 16 and Comparative Example 3 was tested. The testing method was a scratch method. Specifically, a hard steel knife that had been ground to an angle of 30° was used to draw two parallel lines about 2 mm apart on the electrode surface. When drawing the lines, sufficient pressure should be applied to allow a single stroke to pass through the metal coating and cut the underlying metal. Use the naked eye or a 4-5 times magnifying glass to observe whether the coating is peeling or falling off.

[0202] The surface flatness of the first electrode layer after acid treatment of the composite electrodes of Examples 1 to 16 and Comparative Examples 1 to 3 was detected by using AFM to test the surface roughness. The detection results are shown in Table 1.

[0203] The stability of the composite electrodes of Examples 1 to 16 and Comparative Examples 1 to 3 was tested by testing the change rate of the resistance of the composite electrodes after being energized at a current of 2 mA for 5 hours. The test results are shown in Table 1.

[0204] The maximum brightness L of the photoelectric devices of Examples 1 to 16 and Comparative Examples 1 to 3 was measured. max , external quantum efficiency EQE and lifetime T95@1000nit test. See Table 1 for test results.

[0205] Among them, the maximum brightness L max The test method for external quantum efficiency EQE is: using FPD optical property measurement equipment, controlling QE PRO spectrometer, Keithley 2400, and Keithley6485 through LabView, measuring parameters such as voltage, current, brightness, and luminous spectrum, and recording the maximum brightness L max And the external quantum efficiency EQE of the device is obtained by calculation;

[0206] The test method for life span T95@1000nit is: in CDA gas, under constant current or voltage drive, measure the time taken for the device brightness to decay to a certain proportion of the maximum brightness, and the time taken for the brightness to decay to 95% of the maximum brightness is defined as T95, and this life span is the measured life span. In order to shorten the life span test cycle, the device life span test is usually carried out at high brightness by accelerating device aging, and the life span at low brightness is obtained by fitting the decay fitting formula. For example, the life span at 1000nits is recorded as T95@1000nits, and the calculation formula is:

[0207]

[0208] Among them, T95 L The lifespan under low brightness, generally 1000nits, T95 H is the lifespan under high brightness, that is, the measured lifespan, L His the maximum brightness that the device is accelerated to, L L Generally, it is 1000nits, A is the acceleration factor, which is 1.7. The constant current is 2mA.

[0209] Table 1:

[0210]

[0211]

[0212] Among them, “ / ” means not detected.

[0213] From Table 1 we can see that:

[0214] Compared with the composite electrode of Comparative Example 3, the roughness of the first surface of the first electrode layer of the composite electrode of Examples 1 to 16 is significantly higher, and the bonding force between the first electrode layer and the second electrode layer of the composite electrode of Examples 1 to 16 is stronger. It can be seen that the preparation method of the composite electrode of the present application can effectively improve the roughness of the first surface of the first electrode layer, thereby effectively improving the bonding force between the first electrode layer and the second electrode layer, thereby effectively improving the stability of the composite electrode;

[0215] The resistivity change of the composite electrode of Example 1 after being energized for 5 hours at a current of 2 mA is comparable to the resistance change rate of the electrode of Comparative Example 1. However, the composite electrode of the present application adopts a combination of chemical plating and physical plating, which greatly saves the preparation time of the electrode and has better thickness controllability, thus overcoming the uncontrollable thickness phenomenon of pure chemical plating electrodes.

[0216] Compared with the electrode of comparative example 2, the resistance change rate of the composite electrode of example 1 after being energized for 5 hours at a current of 2 mA is smaller. The reason is that the preparation method of the composite electrode of the present application can effectively improve the surface flatness of the electrode compared with pure physical plating, thereby improving the stability of the electrode;

[0217] Compared with the electrode of comparative example 3, the resistance change rate of the composite electrodes of embodiments 1 to 16 after being energized for 5 hours at a current of 2 mA is significantly smaller. The reason is that the first surface 111 of the first electrode layer 11 of the composite electrode of the present application is treated with concentrated sulfuric acid during the preparation process, which effectively improves the binding force of the composite electrode, thereby effectively improving the stability of the composite electrode.

[0218] Compared with the optoelectronic devices of comparative examples 1 to 3, the optoelectronic devices of embodiments 1 to 16 have higher maximum brightness, higher luminous efficiency and longer life. It can be seen that the preparation method of the composite electrode of the present application can effectively improve the conductivity and stability of the composite electrode, thereby improving the maximum brightness, luminous efficiency and life of the optoelectronic device.

[0219] The technical solutions provided by the embodiments of the present application are introduced in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present application. The description of the above embodiments is only used to help understand the method of the present application and its core idea. At the same time, for technical personnel in this field, according to the idea of ​​the present application, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

Claims

1. A method for preparing a composite electrode, characterized in that: The steps include: Providing a substrate and a chemical plating solution, and placing the chemical plating solution on the substrate to obtain a first electrode layer, wherein the first electrode layer includes a first surface; Performing a surface roughening treatment on the first surface of the first electrode layer to obtain a first surface after the surface roughening treatment; The second electrode layer is prepared on the first surface after the surface roughening treatment by physical plating method to obtain a composite electrode.

2. The preparation method according to claim 1, characterized in that The chemical plating solution includes one or more of a silver plating solution, a copper plating solution, a gold plating solution, an aluminum plating solution, and a magnesium plating solution.

3. The preparation method according to claim 1, characterized in that: The chemical plating solution comprises a metal salt, an organic solvent and a reducing agent.

4. The preparation method according to claim 3, characterized in that: The metal salt includes one or more of a silver salt, a copper salt, a gold salt, an aluminum salt and a magnesium salt, wherein the silver salt includes one or more of silver nitrate, silver acetate and silver cyanide, the copper salt includes one or more of copper nitrate, copper acetate and copper cyanide, the gold salt includes one or more of gold nitrate, gold acetate and gold cyanide, the aluminum salt includes one or more of aluminum nitrate, aluminum acetate and aluminum cyanide, and the magnesium salt includes one or more of magnesium nitrate, magnesium acetate and magnesium cyanide; and / or The organic solvent comprises one or more of acetone, methanol and isopropanol; and / or The reducing agent includes one or more of acetaldehyde and hydrazine hydrate; and / or In the chemical plating solution, the mass ratio of the metal salt, the organic solvent and the reducing agent is 1:(2-5):(1-3).

5. The preparation method according to claim 1, characterized in that: After placing the chemical plating solution on the substrate, the method further includes: heating the chemical plating solution on the substrate, wherein the heating temperature is 50 to 70° C., and / or the heating time is 1 to 3 hours.

6. The preparation method according to claim 1, characterized in that: The performing a surface roughening treatment on the first surface of the first electrode layer includes: performing a surface roughening treatment on the first surface of the first electrode layer using concentrated acid.

7. The preparation method according to claim 6, characterized in that: The concentrated acid includes one or more of concentrated sulfuric acid, concentrated nitric acid and concentrated hydrochloric acid; and / or The concentration of the concentrated acid is 1.6 to 4 g / mL; and / or The surface roughening treatment time is 20 to 40 minutes; and / or The roughness of the first surface after the surface roughening treatment is 0.5-1 nm.

8. The preparation method according to claim 1, characterized in that: The physical coating method includes thermal evaporation coating method, electron beam evaporation coating method, magnetron sputtering method, multi-arc ion coating method, physical vapor deposition method, atomic layer deposition method or pulse laser deposition method.

9. The preparation method according to claim 1, characterized in that: The physical coating rate of the physical coating method is 0.1-0.3 nm / s; and / or The physical plating time of the physical plating method is 200 to 300 seconds.

10. The preparation method according to claim 1, characterized in that: The physical plating material used in the physical plating method includes a second metal element, a second alloy or a doped metal oxide, wherein the second metal element includes one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba; the second alloy includes silver-copper alloy, silver-nickel alloy, aluminum-magnesium alloy, aluminum-magnesium-zinc-copper alloy, and gold-magnesium alloy; the doped metal oxide includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide, and cadmium-doped zinc oxide.

11. The preparation method according to claim 1, characterized in that: The chemical plating solution includes a silver plating solution, and the physical plating material used in the physical plating method includes Ag; or The chemical plating solution includes a silver plating solution and a copper plating solution, and the physical plating material used in the physical plating method includes Ag; or The chemical plating solution includes a silver plating solution, and the physical plating material used in the physical plating method includes Al; or The chemical plating solution includes a silver plating solution, and the physical plating materials used in the physical plating method include Ag and Cu; or The chemical plating solution includes a silver plating solution, and the physical plating material used in the physical plating method includes aluminum-doped magnesium oxide.

12. A composite electrode, characterized in that: The invention comprises a stacked first electrode layer and a second electrode layer, wherein the first electrode layer has a first surface, the second electrode layer is combined on the first surface, and the roughness of the first surface is 0.5-1 nm.

13. The composite electrode according to claim 12, characterized in that The thickness of the first electrode layer is in the range of 10 to 30 nm; and / or The thickness of the second electrode layer is in the range of 20 to 90 nm; and / or The material of the first electrode layer includes a first metal element or a first alloy, wherein the first metal element includes one or more of silver, copper, gold, aluminum, and magnesium, and the first alloy includes a silver-copper alloy, a silver-nickel alloy, a silver-magnesium alloy, an aluminum-magnesium alloy, an aluminum-magnesium-zinc-copper alloy, or a gold-magnesium alloy; and / or The material of the second electrode layer includes a second metal element, a second alloy or a doped metal oxide, wherein the second metal element includes one or more of Ag, Ni, Pt, Au, Ir, Cu, Mo, Al, Ca, Mg and Ba, the second alloy includes silver-copper alloy, silver-nickel alloy, aluminum-magnesium alloy, aluminum-magnesium-zinc-copper alloy, and gold-magnesium alloy, and the doped metal oxide includes one or more of indium-doped tin oxide, fluorine-doped tin oxide, antimony-doped tin oxide, aluminum-doped zinc oxide, gallium-doped zinc oxide, indium-doped zinc oxide, magnesium-doped zinc oxide, aluminum-doped magnesium oxide, and cadmium-doped zinc oxide.

14. A method for preparing a photoelectric device, characterized in that: The steps include: providing a substrate, and preparing a first electrode on the substrate; preparing a functional layer on the first electrode; Prepare a second electrode on the surface of the functional layer away from the first electrode to obtain a photoelectric device; Wherein, the first electrode and / or the second electrode is prepared by the preparation method of the composite electrode according to any one of claims 1 to 8.

15. The preparation method according to claim 14, characterized in that: The functional layer includes one or more of a hole injection layer, a hole transport layer, a light emitting layer, and an electron transport layer, wherein: The material of the hole injection layer includes one or more of 2,3,6,7,10,11-hexacyano-1,4,5,8,9,12-hexaazatriphenylene, PEDOT, PEDOT:PSS, PEDOT:PSS doped with s-MoO3 derivatives, 4,4',4'-tris(N-3-methylphenyl-N-phenylamino)triphenylamine, tetracyanoquinodimethane, copper phthalocyanine, nickel oxide, molybdenum oxide, tungsten oxide, vanadium oxide, molybdenum sulfide, tungsten sulfide and copper oxide; and / or The hole transport layer includes materials such as 4,4'-N,N'-dicarbazolyl-biphenyl, poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine], N,N'-diphenyl-N,N'-bis(1-naphthyl)-1,1'-biphenyl-4,4"-diamine, N,N'-diphenyl-N,N'-bis(3-methylphenyl)-(1,1'-biphenyl)-4,4'-diamine, poly(N,N'-bis(4-butylphenyl)-N,N'-bis(phenyl)benzidine), N,N'-bis(3-methylphenyl)-N,N'-bis(phenyl)-spiro, N,N '-bis(4-(N,N'-diphenyl-amino)phenyl)-N,N'-diphenylbenzidine, 4,4',4'-tri(N-carbazolyl)-triphenylamine, 4,4',4'-tri(N-3-methylphenyl-N-phenylamino)triphenylamine, poly[(9,9'-dioctylfluorene-2,7-diyl)-co-(4,4'-(N-(4-sec-butylphenyl)diphenylamine))], poly(N-vinylcarbazole) and its derivatives, N,N'-di(1-naphthyl)-N,N'-diphenyl-1,1'-biphenyl-4-4'-diamine, spiro NPB, poly(phenylene) 1,3-di(carbazol-9-yl)benzene, polyaniline, polypyrrole, poly(p-phenylene vinylene), aromatic tertiary amines, polynuclear aromatic tertiary amines, 4,4'-bis(4-methoxyphenyl)amino)-1,4-phenylene vinylene, 2,2',7,7'-tetrakis[N,N-di(4-methoxyphenyl)amino]-9,9'-spirobifluorene, 4,4'-cyclohexylbis[N,N-di(4-methylphenyl)aniline], ... One or more of (p-carbazolyl)-1,1'-biphenyl compounds, N,N,N',N'-tetraarylbenzidine, PEDOT:PSS and its derivatives, polymethacrylate and its derivatives, poly(9,9-octylfluorene) and its derivatives, poly(spirofluorene) and its derivatives, doped graphene, undoped graphene, C60, doped or undoped NiO, doped or undoped MoO3, doped or undoped WO3, doped or undoped V2O5, doped or undoped P-type gallium nitride, doped or undoped CrO3, doped or undoped CuO; and / or The material of the light-emitting layer includes one or more of an organic light-emitting material and a quantum dot light-emitting material, and the organic light-emitting material includes one or more of 4,4'-bis(N-carbazole)-1,1'-biphenyl:tri[2-(p-tolyl)pyridine iridium(III), 4,4',4"-tri(carbazole-9-yl)triphenylamine:tri[2-(p-tolyl)pyridine iridium, diaromatic anthracene derivatives, distilbene aromatic derivatives, pyrene derivatives, fluorene derivatives, TBPe fluorescent materials, TTPX fluorescent materials, TBRb fluorescent materials, DBP fluorescent materials, delayed fluorescent materials, TTA materials, thermally activated delayed materials, polymers containing covalent bonds of BN, hybrid localized charge transfer excited state materials, exciplex light-emitting materials, polyacetylene and its derivatives, polyparaphenylene and its derivatives, polythiophene and its derivatives, polyfluorene and its derivatives;The quantum dot luminescent material includes one or more of a single structure quantum dot, a core-shell structure quantum dot and a perovskite semiconductor material. The material of the single structure quantum dot, the core material of the core-shell structure quantum dot and the shell material of the core-shell structure quantum dot are independently selected from one or more of II-VI group compounds, IV-VI group compounds, III-V group compounds and I-III-VI group compounds. The II-VI group compounds include CdS, CdSe, CdTe, ZnS, ZnSe, ZnTe, ZnO, HgS, HgSe, HgTe, CdSeS, CdSeTe, CdSTe, ZnSeS, ZnSeTe, Zn STe, HgSeS, HgSeTe, HgSTe, CdZnS, CdZnSe, CdZnTe, CdHgS, CdHgSe, CdHgTe, HgZnS, HgZnSe, HgZnTe, CdZnSeS, CdZnSeTe, CdZnSTe, CdHgSeS, CdHgSeTe, CdHgSTe, HgZnSeS, HgZnSeTe and HgZnSTe, and the IV-VI group compound includes SnS, SnSe, SnTe, PbS, PbSe, PbTe, SnSeS, SnSeTe, SnSTe, PbSeS, One or more of PbSeTe, PbSTe, SnPbS, SnPbSe, SnPbTe, SnPbSSe, SnPbSeTe, SnPbSTe, the III-V group compound includes GaN, GaP, GaAs, GaSb, AlN, AlP, AlAs, AlSb, InN, InP, InAs, InSb, GaNP, GaNAs, GaNSb, GaPAs, GaPSb, AlNP, AlNAs, AlNSb, AlPAs, AlPSb, InNP, InNAs, InNSb, InPAs, InPSb, GaAlNP, GaAlN As, GaAlNSb, GaAlPAs, GaAlPSb, GaInNP, GaInNAs, GaInNSb, GaInPAs, GaInPSb, InAlNP, InAlNAs, InAlNSb, InAlPAs and InAlPSb, the I-III-VI group compound includes one or more of CuInS2, CuInSe2 and AgInS2; the perovskite semiconductor material includes a doped or undoped inorganic perovskite semiconductor or an organic-inorganic hybrid perovskite semiconductor, and the general structural formula of the inorganic perovskite semiconductor is AMX3, wherein A is Cs; + ions, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; the general structural formula of the organic-inorganic hybrid perovskite semiconductor is BMX3, wherein B is an organic amine cation, including CH3(CH2) n-2 NH3 + or [NH3(CH2) n NH3] 2+ , where n≥2, M is a divalent metal cation, including Pb 2+ Sn 2+ , Cu 2+ 、Ni 2+ 、Cd 2+ Cr 2+ , Mn 2+ 、Co 2+ , Fe 2+ ,Ge 2+ , Yb 2+ 、Eu 2+ One or more of, X is a halogen anion, including Cl - Br - ,I - One or more of; and / or The material of the electron transport layer includes one or more of an inorganic electron transport material and an organic electron transport material. The inorganic electron transport material includes one or more of a metal oxide, a doped metal oxide, a IIB-VIA semiconductor material, a IIIA-VA semiconductor material and an IB-IIIA-VIA semiconductor material. The metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO2 and Ta2O5. The metal oxide in the doped metal oxide includes one or more of ZnO, TiO2, SnO2, ZrO2, Ta2O5 and Al2O3. The dopants in the oxide include one or more of Al, Mg, Li, Mn, Y, La, Cu, Ni, Zr, Ce, In, Ga, and Sn; the IIB-VIA semiconductor materials include one or more of ZnS, ZnSe, and CdS; the IIIA-VA semiconductor materials include one or more of InP and GaP; the IB-IIIA-VIA semiconductor materials include one or more of CuInS and CuGaS; the organic electron transport material includes one or more of quinoxaline compounds, imidazole compounds, triazine compounds, fluorene-containing compounds, and hydroxyquinoline compounds.

16. A photoelectric device, comprising a first electrode and a second electrode arranged opposite to each other, and a functional layer arranged between the first electrode and the second electrode, characterized in that: The first electrode and / or the second electrode is prepared by the method for preparing a composite electrode according to any one of claims 1 to 11.

17. The optoelectronic device according to claim 16, characterized in that The functional layer includes one or more of a hole injection layer, a hole transport layer, a light emitting layer, and an electron transport layer.